Toxicology studies of green tea extract in F344/NTac rats and B6C3F1/N mice and toxicology and carcinogenesis studies of green tea extract in Wistar Han [Crl:WI(Han)] rats and B6C3F1/N mice (gavage studies). (Natl Toxicol Program Tech Rep Ser, 2016)
Dried concentrated extracts from Camellia sinensis contain high amounts of catechins and are a popular source for green tea extract nutraceutical supplements and medicinal uses. Supplements containing green tea extract are commonly consumed for weight loss and green tea extracts are popular ingredients in sunblocks, cream rinses, and other cosmetics. Numerous studies in both experimental animals and clinical settings have examined the possible anticancer, anti-inflammatory, antimicrobial, and cardio- and neuroprotective properties of green tea extract. The presumed active ingredient of green tea extract, epigallocatechin gallate (EGCG), was originally nominated by the National Cancer Institute for toxicity and carcinogenicity studies because it is the most abundant catechin in green tea extract, it was being investigated as a potential chemotherapeutic agent, and there was a lack of adequate information with regard to its toxicity. However, the NTP selected green tea extract [containing EGCG (48.4% by weight) and other green tea catechins] for study because human exposure is to green tea extract products that contain concentrated mixtures of various green tea catechins. The NTP analyzed four lots of green tea extract and selected a source based on quantities of EGCG, consistency with other products on the market, and availability in bulk quantity. Oral gavage was chosen as the route of administration because it was considered most relevant to human exposure. Male and female F344/NTac rats and B6C3F1/N mice were administered green tea extract in water by gavage for 3 months and male and female Wistar Han [Crl:WI(Han)] rats (referred to as Wistar Han rats) and B6C3F1/N mice were administered green tea extract in water by gavage for 2 years. Genetic toxicology studies were conducted in Salmonella typhimurium, Escherichia coli, and mouse peripheral blood erythrocytes. (Abstract Abridged).